2019
DOI: 10.1002/cmdc.201900596
|View full text |Cite
|
Sign up to set email alerts
|

Highly Porous Hybrid Metal–Organic Nanoparticles Loaded with Gemcitabine Monophosphate: a Multimodal Approach to Improve Chemo‐ and Radiotherapy

Abstract: Nanomedicine recently emerged as a novel strategy to improve the performance of radiotherapy. Herein we report the first application of radioenhancers made of nanoscale metal‐organic frameworks (nanoMOFs), loaded with gemcitabine monophosphate (Gem‐MP), a radiosensitizing anticancer drug. Iron trimesate nanoMOFs possess a regular porous structure with oxocentered Fe trimers separated by around 5 Å (trimesate linkers). This porosity is favorable to diffuse the electrons emitted from nanoMOFs due to activation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 57 publications
6
18
0
Order By: Relevance
“…This is in line with previous studies showing the efficient internalization of nanoMOFs bearing or not a lipid coating in pancreatic, breast, or bladder cancer cell lines (Rodriguez-Ruiz et al, 2015;Wuttke et al, 2015;Li et al, 2019a). It was recently shown that nanoMOFs acted as "Trojan horses" internalized by cancer cells, carrying their Gem-MP cargo to interfere with DNA (Li et al, 2019a). In this study it was shown that interestingly, the presence of a lipid coating (PEGylated or not) did not reduce the nanoMOF anticancer efficacy on SKOV3 ovarian cancer cells.…”
Section: Cytotoxicity Assays Of Nanomofs On Ovarian Cancer Cellssupporting
confidence: 92%
See 3 more Smart Citations
“…This is in line with previous studies showing the efficient internalization of nanoMOFs bearing or not a lipid coating in pancreatic, breast, or bladder cancer cell lines (Rodriguez-Ruiz et al, 2015;Wuttke et al, 2015;Li et al, 2019a). It was recently shown that nanoMOFs acted as "Trojan horses" internalized by cancer cells, carrying their Gem-MP cargo to interfere with DNA (Li et al, 2019a). In this study it was shown that interestingly, the presence of a lipid coating (PEGylated or not) did not reduce the nanoMOF anticancer efficacy on SKOV3 ovarian cancer cells.…”
Section: Cytotoxicity Assays Of Nanomofs On Ovarian Cancer Cellssupporting
confidence: 92%
“…At equivalent Gem-MP concentrations, whatever the drug loading (8 or 20 wt%) and the amount of nanoMOF in contact with the cells (10 to 100 µg/mL), the drug-loaded nanoMOFs outperformed the free drug in terms of toxicity on cancer cells (Figure 7 and Supplementary Figure S5). This is in line with previous studies showing the efficient internalization of nanoMOFs bearing or not a lipid coating in pancreatic, breast, or bladder cancer cell lines (Rodriguez-Ruiz et al, 2015;Wuttke et al, 2015;Li et al, 2019a). It was recently shown that nanoMOFs acted as "Trojan horses" internalized by cancer cells, carrying their Gem-MP cargo to interfere with DNA (Li et al, 2019a).…”
Section: Cytotoxicity Assays Of Nanomofs On Ovarian Cancer Cellssupporting
confidence: 91%
See 2 more Smart Citations
“…Organic compounds remain the most employed materials for drug incorporation and for engineering multifunctional shells. Additionally, the presence of metals in drug nanocarriers' composition offers new functionalities, such as antibacterial or antifungal properties, [7] radioenhancement [8] or imaging abilities for personalized therapies. [9] More recently, nanoscale hybrid metal-organic frameworks (MOFs) emerged as versatile Drug nanocarriers (NCs) with sizes usually below 200 nm are gaining increasing interest in the treatment of severe diseases such as cancer and infections.…”
mentioning
confidence: 99%